1966
DOI: 10.1136/gut.7.1.86
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical study on the Paneth cell in the rat.

Abstract: EDITORIAL SYNOPSIS The characteristic granules of this cell fulfil the enzymatic criterion of lysosomes.The function of the Paneth cell has more than once been investigated since its discovery in 1872 by Schwalbe. A complete review of available information was presented by Patzelt (1936 (Baker, 1956) and by the diazotisation-coupling method (Glenner and Lillie, 1959); and tryptophan by the method of Adams (1957). These reactions were carried out on freeze-dried formaldehydevapour-fixed material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

1970
1970
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 35 publications
0
11
0
3
Order By: Relevance
“…Hally [14] could find no evidence that the electron dense lysosomes are either discharged into the crypt lumen or transformed directly into secretory granules. Riecken and Pearse [31] showed that enzyme activity in the Paneth cell was at its weakest in the region of the secretory granules, and strongest in the region of the Golgi apparatus where the electron dense bodies are found. This observa tion receives confirmation from Lewin [21] who found some aminopeptidase in the Paneth cell, but not localised to the secretory granules.…”
Section: Discussionmentioning
confidence: 99%
“…Hally [14] could find no evidence that the electron dense lysosomes are either discharged into the crypt lumen or transformed directly into secretory granules. Riecken and Pearse [31] showed that enzyme activity in the Paneth cell was at its weakest in the region of the secretory granules, and strongest in the region of the Golgi apparatus where the electron dense bodies are found. This observa tion receives confirmation from Lewin [21] who found some aminopeptidase in the Paneth cell, but not localised to the secretory granules.…”
Section: Discussionmentioning
confidence: 99%
“…No C c. yacare não observamos as primeiras, mas enormes glândulas ovais, lobuladas entre o conjuntivo subepitelial e a camada muscular. Vários autores descreve· ram glândulas lobulares, holócrinas em crocodilianos (RIEKEN & PEARSE, 1966;VOELTSKOW, 1902;DISSELHORST, 1904;TAGUCHl, 1920;BAKER, 1942). Parece que essas glândulas estão relacionadas com a maturidade e estimulação sexual.…”
Section: Discussão E Conclusõesunclassified
“…RIEcKEN and PEARSE (1966) suggested that the Paneth cell secretory granules are lysosomal in function, because of their positive cytochemical reactivities for lysosomal enzymes such as acid phosphatase and esterases. It has been well established that one of the main substances contained in the Paneth cell secretory granules is lysozyme (see review by SANDOW and WHITEHEAD, 1979;HEITZ and WEGMANN, 1980; LOPEZ-LEWELLYN and ERLANDSEN, 1980;RODNING et al, 1982).…”
Section: Discussionmentioning
confidence: 99%